2020
DOI: 10.18632/aging.103677
|View full text |Cite
|
Sign up to set email alerts
|

piR-19166 inhibits migration and metastasis through CTTN/MMPs pathway in prostate carcinoma

Abstract: Tumor metastasis is one of death causes for patients of prostate carcinoma. PIWI-interacting RNAs (piRNAs) are a subtype of noncoding protein RNAs that are involved in tumorigenesis, but the effect of piRNAs in prostate carcinoma (PCa) remains unclear. This article showed the identification of piRNAs was performed using a piRNA microarray screen in PCa tissues and several piRNAs were identified as dysregulated. The two up-regulated piRNAs (piR-19004 and piR-2878) and one down-regulated piR-19166 have been vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In addition, EVs secreted from tumor cells may contain a variety of piRNAs originating from tumor cells, which may be aberrantly expressed in tumor cells [29]. Early evidence showed that piRNAs are involved in PCa development and progression, such as proliferation, apoptosis, metastasis, and invasion [19,20,30]. However, the diagnostic value of piRNA for PCa diagnosis has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, EVs secreted from tumor cells may contain a variety of piRNAs originating from tumor cells, which may be aberrantly expressed in tumor cells [29]. Early evidence showed that piRNAs are involved in PCa development and progression, such as proliferation, apoptosis, metastasis, and invasion [19,20,30]. However, the diagnostic value of piRNA for PCa diagnosis has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, modulating the expression of piRNAs may reverse these phenotypes. As for PCa, several recent studies revealed that piRNAs were involved in the proliferation, migration, and invasion of PCa cells by conducting different signal pathways, which may represent a new marker of PCa diagnosis [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the piRNA-30473/WTAP/HK2 axis promotes the occurrence of breast cancer by regulating the methylation of m6A RNA in diffuse large B-cell lymphoma[ 34 ]. piRNA-19166 inhibits cell migration and metastasis through the cortactin/mitochondrial membrane potential pathway in prostate cancer[ 35 ]. piRNA-823 promotes the angiogenesis of endothelial cells by promoting the secretion of VEGF and interleukin -6.…”
Section: Discussionmentioning
confidence: 99%
“…Transfection of PCa cells by piR_19166 suppressed migration and metastasis via CTTN/matrix metalloproteinases (MMPs) pathway in PCa cells. Authors propose that piR_19166, through regulation of the oncogene CTTN, inhibits migration and distant metastasis of prostate cancer cells and may represent a new marker of diagnosis and treatment for PCa patients in early stages [ 196 ].…”
Section: The Role Of Pirnas In Gcmentioning
confidence: 99%